HAKIKAT EVALUASI DALAM PENDIDIKAN ISLAM - Syarnubi, Syarnubi (PAI RAFAH, 2023)
Education is an activity that seeks to obtain knowledge that humans initially did not know so that they know. Starting from education, people begin to know the world, uncovering new discoveries that were previously unknown to people. In line with the existence of an activity, there must be an evaluation of that activity. Education is an activity that has been arranged through the applicable curriculum, the final activity of an education is evaluation (assessment). Educational evaluation is very necessary in education, among others, providing information that is used as a basis for: 1. Making policy and decisions. 2. Assessing the results achieved by students. 3. Assess the curriculum. 4. Giving trust to the school. 5. Monitor the funds that have been given. 6. Improve education materials and programs. The evaluation results on the world of national education are quite alarming, not only in terms of quality but also failure in shaping the character of the nation's young generation. Education is the responsibility of all parties, where the goal of education is to humanize humans. Form high-quality human resources. The success or failure of Islamic education in achieving its goals can be seen after evaluating the output it produces. If the results are in accordance with what has been outlined in the objectives of Islamic education, then the educational effort can be considered successful, but if the opposite is true, then it is considered a failure. From this perspective, it can be understood how urgent evaluation is in the Islamic education process.